The Effect Of Suggested Exercises On Developing Some Mental Abilities For Children Aged 4-6 Years - Rabeea, Mohammed Saad; Khalifa, Abbas Hussein; Obaid, Mustafa Ahmed (مجلة دراسات وبحوث التربية الرياضية, 2024)
The purpose of the current article lies in determining the impact of the suggestive exercises on the development of the mental capabilities of children. The researchers used the experimental method with a single-group design, which was appropriate for the core of the current article . The study samble has been specified as children aged 4-6 years in Umm Al-Rabi'een Kindergarten, with a total of 95 children. The study samble (15 children) was randomly selected. . After the exercises were completed, the post-tests have been carried out on the sample with similar circumstances as that of pre-tests. Researchers used statistical methods in the SPSS program. After the results were presented, analyzed, and discussed, The researchers concluded that the exercises conducted for the children had a positive effect on how to use and improve the children's mental abilities.